Consumer Preference for Genetically Modified Halal Yogurt Drinks - Hassan, Siti Hasnah; Iqbal, Qaisar (UI Scholars Hub, 2021)
This study strives to understand the importance placed by consumers on the features of a product when purchasing yogurt drinks. In addition, their attitude towards genetically modified foods, generally, and their purchase intention towards genetically modified yogurt drinks, in particular, was also determined. Convenience sampling was employed; 120 usable responses were received from the self-administered survey. The research findings showed that nutrition was deemed as being the most important product feature that influenced the decision in purchasing yogurt drinks. This was followed by freshness, price, flavor, variety, and origin. Furthermore, it was found that respondents presented a neutral attitude and purchase intention towards genetically modified yogurt drinks. The recommendations to market practitioners, research limitations, as well as suggestions for future studies are also discussed.